Designing Effective Insolvency Frameworks for Multinational Corporations: A Literature Review on Reform Priorities and Value Foundations in Developing Countries - Cahyatih Kumandang; Mia Christy Patricia (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2026)
This study conducts a qualitative literature review to examine how insolvency frameworks in developing countries can be designed to effectively accommodate multinational corporations (MNCs). Drawing on interdisciplinary legal, economic, and policy oriented scholarship, the review analyses why MNCs frequently avoid initiating insolvency proceedings in host developing jurisdictions and instead engage in forum shopping toward developed economies. The findings indicate that institutional weaknesses, limited judicial and professional capacity, inadequate group-insolvency coordination, and low procedural predictability significantly reduce the attractiveness of domestic insolvency regimes. The review further identifies core value foundations legal certainty, transparency, efficiency, stakeholder balance, and enterprise value preservation as essential elements of effective insolvency law reform. The study contributes by synthesising reform priorities that move beyond formal legislative change toward strengthening institutional credibility and normative legitimacy, offering policy relevant insights for developing countries seeking to retain multinational insolvency cases and enhance economic resilience.